Impact of wedge-shaped design for building bottlenecks on evacuation time for efficiency optimization. (November 2015) - Mu, H L; Lo, S M; Song, W G; Lv, W; Sun, J H
In order to ensure people's safety during the evacuation process in an emergency, it is important to improve evacuation efficiency, particularly to reduce the egress time. In the present study, a wedge-shaped design for building bottleneck spaces, including exits, passageways, and joints of intersection, is proposed and described. Furthermore, through numerical simulation using a social force model, the impact of the wedge design on the evacuation time of occupants is investigated. It can be found that the evacuation time is reduced with the wedge design compared to a rectangular design under the same conditions. The effects of the short-side length and angle of wedge ( β ) are also examined. For the different short-side lengths studied (0.8 and 1.0 m), the mean difference in the evacuation time-saving rate increases at a relatively steady rate with the increase in the long-side length. In addition, simulation results indicate the maximum evacuation time-saving rate appears when β ranges between 45° and 53.13°. It is hoped that the results will serve as basic reference to improve relevant engineering construction of building spaces and management of emergency evacuations.